Creatively, art educates - Sobrinho, Asdrúbal Borges Formiga; Sanmartin, Stela Maris; Cirilo, Aparecido José (Farol, 2024)
This text discusses the specificities of the field of art and creativity to reflect on what it can teach for education, in order to modify teaching-learning processes. Here we review concepts of creativity in the educational context, proposing the case study as a method for investigations that allow access to the uniqueness of art students. With this, it is hoped that both the researched, as well as the researchers and educators, can exercise their creative potential and contribute to changes in education, culture and society.